2014
DOI: 10.1002/2013jc009592
|View full text |Cite
|
Sign up to set email alerts
|

Coherent intraseasonal oceanic variations in the eastern equatorial Indian Ocean and in the Lombok and Ombai Straits from observations and a high‐resolution OGCM

Abstract: Ongoing acoustic Doppler current profilers (ADCP) observation in the eastern equatorial IndianOcean and a recent International Nusantara Stratification and Transport (INSTANT) experiment in the Indonesian Throughflow (ITF) straits have shown coherent intraseasonal oceanic variations in this region. The intraseasonal variations are dominated by 30-70 day variations, with a tendency for the observed currents in the eastern equatorial Indian Ocean to lead those at the Lombok and Ombai Straits. Phase speed of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…The Indonesian Throughflow cools and freshens the eastern Indian Ocean [Gordon, 2005]. Indian Ocean Kelvin waves forced by westerly wind bursts (section 3.3.4) are partially transformed to coastal Kelvin waves, where they can modulate the Throughflow [Gordon, 2005;Sprintall et al, 2009;Gordon et al, 2010;Drushka et al, 2010;Sprintall et al, 2010;Iskandar et al, 2014] and tidal mixing [e.g., Schiller et al, 2010]. From the perspective of MJO convection, the Maritime Continent presents reduced ocean area, steep island terrain, and strongly forced diurnal convection, all of which may interfere with the intraseasonal convection and associated air-sea interactions.…”
Section: Air-sea Interactions In Other Tropical Regions and Seasonsmentioning
confidence: 99%
“…The Indonesian Throughflow cools and freshens the eastern Indian Ocean [Gordon, 2005]. Indian Ocean Kelvin waves forced by westerly wind bursts (section 3.3.4) are partially transformed to coastal Kelvin waves, where they can modulate the Throughflow [Gordon, 2005;Sprintall et al, 2009;Gordon et al, 2010;Drushka et al, 2010;Sprintall et al, 2010;Iskandar et al, 2014] and tidal mixing [e.g., Schiller et al, 2010]. From the perspective of MJO convection, the Maritime Continent presents reduced ocean area, steep island terrain, and strongly forced diurnal convection, all of which may interfere with the intraseasonal convection and associated air-sea interactions.…”
Section: Air-sea Interactions In Other Tropical Regions and Seasonsmentioning
confidence: 99%
“…High-resolution modelling studies have suggested that the intra-seasonal variability has a time scale of 30-60 days (e.g. Iskandar et al (2006Iskandar et al ( , 2014) and the only known mooring data in this region shows deep fluctuations in this current to last at least a couple of weeks (see Figs. 2b-d of Sprintall et al (1999)).…”
Section: Crossover Analysis and Cross-calibrationmentioning
confidence: 99%
“…The significant correlations and respective time lags (Table ) suggested that the signals were propagated along the coasts by coastal Kelvin waves, as discussed by Iskandar et al . [].…”
Section: Data and Processingmentioning
confidence: 99%
“…Each correlation was statistically significant at the 99% level and the correlation coefficient of two adjacent stations was high (>0.7), which suggested that the observational data were reliable. The significant correlations and respective time lags (Table 1) suggested that the signals were propagated along the coasts by coastal Kelvin waves, as discussed by Iskandar et al [2014].…”
Section: Sea Level Datamentioning
confidence: 99%